2010
DOI: 10.1128/iai.00465-10
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C θ Deficiency Increases Resistance of C57BL/6J Mice toPlasmodium bergheiInfection-Induced Cerebral Malaria

Abstract: Protein kinase C (PKC) functions as a core component of the immunological synapse and serves as a key protein in the integrated T-cell antigen receptor (TCR)/CD28-induced signaling cascade leading to T-cell activation. However, the involvement of PKC in host-mediated immune responses to pathogens has not been thoroughly investigated. We tested the consequences of PKC ablation on the host response to infection by Plasmodium berghei ANKA (PbA). We found that both PKC ؉/؉ and PKC ؊/؊ C57BL/6J mice are susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…37 To address the role of PKC-in CM pathogenesis, PKC--deficient mice were investigated for several aspects of the pathophysiology of CM development. The present study demonstrated protection of PKC--deficient mice against CM after infection with PbA, in agreement with the recent study of Ohayon et al, 38 who also demonstrated that PKChas an effect on CM development; however, dissociated were the CM and the lung disease that are not affected by PKC-deficiency. Most PKC--deficient mice survived beyond day 15 without signs of CM.…”
Section: Discussionsupporting
confidence: 93%
“…37 To address the role of PKC-in CM pathogenesis, PKC--deficient mice were investigated for several aspects of the pathophysiology of CM development. The present study demonstrated protection of PKC--deficient mice against CM after infection with PbA, in agreement with the recent study of Ohayon et al, 38 who also demonstrated that PKChas an effect on CM development; however, dissociated were the CM and the lung disease that are not affected by PKC-deficiency. Most PKC--deficient mice survived beyond day 15 without signs of CM.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is generally accepted that the same immunological response contributes to malaria pathogenesis, with a local organ-specific inflammatory response initiated by the presence of parasite and sustained by infiltrating cells within the vasculature [2], [15], [36]–[39]. In this work, we describe an important new role for an AT 1 receptor-mediated effect of Ang II in T cell activation, migration and adhesion during P. berghei ANKA infection.…”
Section: Discussionmentioning
confidence: 87%
“…The expression of CD11a (LFA-1), an adhesion molecule expressed in activated T cells during P. berghei ANKA infection, was analyzed by flow cytometry [39]. P. berghei ANKA infection upregulates CD11a expression in splenic T cells and treatment with losartan or captopril partially inhibited it (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the ability of innate immunity signals to bypass the requirement for protective responses to pathogens may not be generalizable or absolute. In fact, studies demonstrated that the immune response against two unicellular protozoan parasites, Toxoplasma gondii (Nishanth, et al, 2010) or Plasmodium berghei (Ohayon, et al, 2010) was impaired in Prkcq −/− mice, reflecting defects in both Th1 and Th2 cytokines. The primary defect in these infections may lie in impaired activation of innate TLR signaling pathways (Griffith, et al, 2007; Yarovinsky, et al, 2005), with the subsequent adaptive immunity defect representing a secondary phenomenon.…”
Section: The Differential Role Of Pkcθ In Immune Responsesmentioning
confidence: 99%